Role of Libraries in Human Flourishing: Adolescents’ Motivational Orientation for Occupation - Yusuke Matsuyama (MDPI AG, 2021)
Introduction: Adolescence is crucial for human flourishing and strongly influences having meaning in life. We investigated the association between local public library density as a shared resource and motivational orientation toward their occupation in Japanese adolescents. Methods: A longitudinal study was conducted using data from a nationwide birth cohort survey in Japan (n = 12,184). At age 7, their caregivers answered questionnaires on children including the number of books read. Library density (low, moderate, or high) in each municipality was obtained from national statistics. At age 15, the adolescents indicated whether they had decided on an occupation and selected motivational orientations from among intrinsic (own ability and interest), extrinsic (high earnings, social class, or job stability), and altruistic (social contribution) orientations. Multilevel linear probability models were fitted, adjusting for confounders, including household socioeconomic status and city size. Results: Intrinsic, extrinsic, and altruistic motivations for desired occupation were reported by 40.7%, 31.9% and 41.8% of participants, respectively. Living in a municipality with a high library density at age 7 was associated with having intrinsic motivation at age 15 than low density by 3.1 percentage points (95% confidence interval (CI): 0.35, 5.85). The association was more prominent for those with lower income (P for interaction = 0.026). Neither extrinsic nor altruistic motivations were associated with library density (coefficient: −0.13; 95% CI: −2.81, 2.56; coefficient: 0.08; 95% CI: −2.72, 2.88 percentage points, respectively). Conclusions: Developing libraries in communities could encourage intrinsic motivation in adolescents, specifically for those in low-income households.